Integrated project-based e-learning with science, technology, engineering, arts, and mathematics (PjBeL-STEAM): its effect on science process skills - Mufida, Siti Nur; Sigit, Diana Vivanti; Ristanto, Rizhal Hendi (Universitas Negeri Jakarta, 2020)
This research aims to analyze the effect of the project-based e-learning with science, technology, engineering, arts, and mathematics (PjBeL-STEAM) learning model on students’ science process skills. The PjBeL-STEAM learning model emphasizes on project activities with interdisciplinary through online learning. The research employs a quasi-experimental method with a pretest-posttest control group design. The research population includes students of grade X in ecosystem learning at one of public senior high schools in Jakarta Timur, Indonesia. The research sample consists of 72 students taken using purposive sampling. The main projects in PjBeL-STEAM learning include creating an animation of biogeochemical cycles and independent experiments. The research data on science process skills are collected using pretest and posttest questions. Students’ response to learning uses Likert scale instruments. The data analysis technique employs an Independent sample t-test. The research results indicate that the PjBeL-STEAM learning model provides better effects on science process skills than in control class. It is necessary to implement the PjBeL-STEAM learning model in online Biology learning to improve science process skills in better ecosystem learning.